Vascular function in adults with cyanotic congenital heart disease. (October 2020) - Tarp, Julie Bjerre; Clausen, Peter; Celermajer, David; Christoffersen, Christina; Jensen, Annette Schophuus; Sørensen, Keld; Sillesen, Henrik; Estensen, Mette-Elise; Nagy, Edit; Holstein-Rathlou, Niels-Henrik; Engstrøm, Thomas; Feldt-Rasmussen, Bo; et al.
Abstract: Background: Patients with cyanotic congenital heart disease (CCHD) may have a low burden of atherosclerosis. Endothelial dysfunction is an early stage of atherosclerosis and endothelial function is previously studied in smaller CCHD groups with different techniques and variable results. We aimed to examine endothelial function and carotid atherosclerosis in a larger group of CCHD patients. Methods: This multicentre study assessed endothelial function in adults with CCHD and controls by measuring the dilatory response of the brachial artery to post-ischemic hyperaemia (endothelium-dependent flow-mediated-vasodilatation (FMD)), and to nitroglycerin (endothelium-independent nitroglycerin-induced dilatation (NID)). Flow was measured at baseline and after ischaemia (reactive hyperaemia). Carotid-intima-media-thickness (CIMT), prevalence of carotid plaque and plaque thickness (cPT-max) were evaluated ultrasonographically. Lipoproteins, inflammatory and vascular markers, including sphingosine-1-phosphate (S1P) were measured. Results: Forty-five patients with CCHD (median age 50 years) and 45 matched controls (median age 52 years) were included. The patients presented with lower reactive hyperaemia (409 ± 114% vs. 611 ± 248%, p < 0.0001), however preserved FMD response compared to controls (106.5 ± 8.3% vs. 106.4 ± 6.1%, p = 0.95). In contrast, NID was lower in the patients (110.5 ± 6.1% vs. 115.1 ± 7.4%, p = 0.053). There was no difference in CIMT, carotid plaque or cPT-max. The patients presented with lower high-density-lipoprotein cholesterol, and higher level of inflammatory markers and S1P. Conclusion: Adults with CCHD had preserved FMD in the brachial artery, but impaired NID response and lower reactive hyperaemia than controls. The preserved FMD and the comparable prevalence of carotid atherosclerosis indicate that CCHD patients have the same risk of atherosclerosis as controls.